School-Associated Violent Deaths in the United States: A Comprehensive Review of the Literature. (2nd October 2022) - Stewart, Ilaria; Wertz, Joseph; Jen, Howard
ABSTRACT: Despite its rarity, school-associated violent death (SAVD) has wide-ranging implications on school safety, education quality, public health, politics, and more. This review article summarizes the data sources most used to surveil and study SAVD, the novel findings and recurring themes of original SAVD research, and the persisting gaps in SAVD research today. Overall, we found that academic attention and productivity related to SAVD has not focused on the most prevalent subtype – single-victim homicides occurring in urban, public schools and involving Black and Hispanic offenders and victims. Instead, the majority of SAVD research has focused on the much less frequent yet more conspicuous "rampage" multiple-victim homicides. Similarly, we identified an extraordinary dearth of both surveillance and research on all other types of SAVD, especially suicide and non-firearm violent death.